The Georgian Translations of Andrew of Crete's Great Canon and Some Aspects of the Canon's Establishment as a Genre - Laura Grigolashvili (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
Andrew of Crete's Great Canon is one of the oldest and most important monuments of Christian spiritual heritage. There are several factors that make this masterpiece of hymnology particularly important for Georgian liturgical and hagiographical scholarship. The Hymns of Repentance by the great David Aghmashenebeli (David IV the Builder, 1073, 24 January 1125), King of Georgia, are inspired by this Canon. In addition, the names of three of the most notable representatives of Georgian literature, Ekvtime Mtatsmideli (St. Euthymius the Hagiorite), Giorgi Mtatsmideli (George the Hagiorite, George the Athonite), and Arsen Iqaltoeli (Arsen of Iqalto), are associated with this work; they have all translated St. Andreas' Canon of Repentance and have established it as one of the most important and monumental works of the Christian liturgical poetry in Georgia. Beyond these historical indications, as the current reevaluation of asceticism as both a religious-mystical experience and a unique phenomenon in itself is taking place, the Canon is particularly relevant in todays world. Even the representatives of Poststructuralism and Postmodernism have taken interest in the essence of Askesis, recognizing it as a positive occurrence. Furthermore, asceticism is regarded as the universal prerequisite of a culture as it is, as a basis that largely determines relationships between cultures and creates possibilities of initiating communications between them. It is widely recognized that the foundations of universal ethics are highlighted precisely in ascetic literature and that todays intellectual elite cannot add anything new to these principles.